2012
DOI: 10.1007/s11302-012-9345-0
|View full text |Cite
|
Sign up to set email alerts
|

Ecto-nucleotidases distribution in human cyclic and postmenopausic endometrium

Abstract: Extracellular ATP and its hydrolysis product, adenosine, acting through specific receptors collectively named purinergic receptors, regulate female fertility by influencing the endometrial fluid microenvironment. There are four major groups of ecto-nucleotidases that control the levels of extracellular ATP and adenosine and thus their availability at purinergic receptors: ecto-nucleoside triphosphate diphosphohydrolases (E-NTPDases), ecto-nucleotide pyrophosphatase/phospho-diesterases (E-NPPs), ecto-5′-nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 47 publications
4
41
1
Order By: Relevance
“…The highest levels of expression are seen in the uterine epithelium and in the seminal vesicles, pointing to its likely importance in reproductive biology [50,57]. Recently the various ecto-nucleases were surveyed in human endometrium, and ENPP3 was found to be specifically elevated in the secretory phase of the menstrual cycle [59]. The increased secretory expression of ENPP3 was recently described to be blunted in a progestin-resistant manner from the eutopic endometrium from women with endometriosis.…”
Section: Hood Et Almentioning
confidence: 99%
“…The highest levels of expression are seen in the uterine epithelium and in the seminal vesicles, pointing to its likely importance in reproductive biology [50,57]. Recently the various ecto-nucleases were surveyed in human endometrium, and ENPP3 was found to be specifically elevated in the secretory phase of the menstrual cycle [59]. The increased secretory expression of ENPP3 was recently described to be blunted in a progestin-resistant manner from the eutopic endometrium from women with endometriosis.…”
Section: Hood Et Almentioning
confidence: 99%
“…In a later paper, these authors showed that the P2Y 2 receptor is expressed by stromal cells, suggesting that it mediates the expression of the early growth response 1 and inhibits stromal cell viability [77]. The distribution of ecto-nucleotidases in human cyclic and post-menopausic endometrium has been described [8]. Ecto-NPP3 was identified as a new biological marker of tubal metaplasia.…”
Section: Myometriummentioning
confidence: 99%
“…Immunohistochemistry experiments were performed as described previously [24] except for the use of 30-μm-thick free-floating slices. Slices were incubated overnight at 4°C with the following anti-human-monoclonal antibodies: CD39 (1:500; Ancell, Minnesota, USA), hN3-B3 S for NTPDase3 (1:500; http://ectonucleotidases-ab.com/) and CD73 (1:50; Hycult biotechnology, Uden, The Netherlands).…”
Section: Immunohistochemistry Experimentsmentioning
confidence: 99%
“…Histochemical localization of ATPase, ADPase, and AMPase activity was carried out using the Wachstein/Meisel lead phosphate method [24][25][26] in cryostat-obtained (30-μm thick) free-floating slices. Enzymatic reaction was measured [27].…”
Section: In Situ Activity Experimentsmentioning
confidence: 99%
See 1 more Smart Citation